New applications of photolabile nitrobenzyl groups in polymers. - Thomas, Samuel W., III. (Tufts University. Tisch Library., 2018)
This article describes progress in the author's laboratory in two new areas of photoresponsive polymers: (1) photochemical control of electrostatics, and (2) conjugated materials with photocleavable pendants. In both cases, incorporation of o-nitrobenzyl esters (NBEs) imparts this photoreactivity. NBE-derivatized, ring-opening metathesis polymerization (ROMP)-derived polycations form positive photoresist layer-by-layer (LbL) films that dissolve in base upon irradiation. NBE-derivatized conjugated oligomers show photoactivated fluorescence, whereas NBE-substituted polythiophenes are negative photoresists due to photolysis of solubilizing alkyl chains.